Secure Trust-Based Algorithm using Blockchain Technology to Prevent Attacks in VANET - Kuhanraj, Balan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Vehicular Ad hoc Networks (VANET) is also known as intelligent transportation systems. VANET ensures timely and accurate communications between vehicle to vehicle and vehicle to infrastructure to improve road safety and enhance the efficiency of traffic flow. Due to open wireless boundary and high mobility, VANET is vulnerable to malicious nodes that could gain access into the network and carry out serious network threats such as denial of service attack, data modification attack, impersonation attack, Sybil attack and replay attack. This could affect the network security and privacy, causing harm to the information exchange within the network and increase fatal impacts on the road. Therefore, a secure trust-based mechanism that utilizes blockchain technology has been proposed to increase security and privacy while minimising the aforementioned attacks. A series of experiment has been conducted using Veins simulation tool to assess the performance of the proposed solution in the terms of packet delivery ratio, end to end delay, packet loss and transmission overhead. The simulation results show that under network attack, the proposed solution incurs a better packet delivery ratio at 0.75, smallest percentage of packet loss at 25.5%, a shorter end to end delay of 0.13 seconds and lesser transmission overhead at 5.0% as compared to existing protocols.